Successful Therapy for a Mixed Thyrotropin- and Prolactin-Secreting Pituitary Macroadenoma With Cabergoline - Mulinda, James; Hasinski, Stefan; Rose, Leslie I. (Endocrine Practice, 1999)
To describe the first case of a mixed thyrotropin (TSH)- and prolactin-secreting pituitary macroadenoma that responded to therapy with cabergoline. We present a case report with clinical, laboratory, and radiologic details. An 84-year-old woman with central hyperthyroidism due to a mixed TSH- and prolactin-secreting pituitary macroadenoma was successfully treated with orally administered cabergoline, 0.25 mg twice per week. Serial assays of thyroid and pituitary hormones were done, and magnetic resonance imaging of the pituitary was performed before and 16 weeks after initiation of cabergoline therapy. The patient had complete resolution of the increased pituitary hormone indices within 6 weeks after implementation of therapy, and these results were sustained for more than 16 weeks. A magnetic resonance imaging scan showed no change in tumor size at 16 weeks of therapy. When medical treatment of TSH-secreting tumors is considered, choices of efficacious drugs are limited. To our knowledge, this report describes the first case of a long-acting dopamine agonist used successfully to control hypersecretion of a mixed TSH- and prolactin-secreting macroadenoma. Oral administration of cabergoline twice a week was effective, convenient, and well tolerated. Further evaluation of cabergoline, when indicated as medical therapy for TSH-secreting tumors, is warranted. (Endocr Pract. 1999;5:76-79)
Keywords: Prolactin-Secreting Pituitary Macroadenoma; Mixed Thyrotropin; Successful Therapy